UDP4US: Universal Device Pipe for Ubiquitous Services - Felisberto, Thiago Zanivan; Tramontin, Elder Dominghini; Santos, Felipe Da Cunha Dos; Morales, Analucia Schiaffino; Siqueira, Frank; Araujo, Gustavo Medeiros De (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2015: Anais do V Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2015)
The growing evolution in the development of embedded systems has raised a numerous amount of distributed applications. Such applications have a strong tendency to integrate various types of existing devices. This trend is aligned with the ideas of ubiquitous computing, which is expected to turn devices increasingly independent of people, making the relationship between technologies more natural and intuitive. The different communication rotocols used by these devices target a specific segment, such as multimedia sharing, electronic security, home automation and healthcare. However, this variety increases the complexity of device integration and represents an obstacle to their development. This paper presents an architecture capable of providing compatible services that can be requested using heterogeneous protocols and is based on the fundamentals of the service-oriented architecture. The central component of this architecture is a middleware capable of abstracting requests of different protocols, facilitating dynamic composition of services distributed in heterogeneous LAN. The proposed architecture is detailed in this article. In addition, several experiments were conducted to evaluate the performance of the proposed middleware, in pursuit of their boundaries and aiming to validate the adopted technologies. As far as we know, our work is the first one that provides interoperation between the DLNA and DPWS technologies.